Cohesive Devices in Learnersâ Writing - Nugraheni, Ratnasari (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
In ESL context, learners may have less attention to the use of conjunctions. In fact, theÂ use of conjunctions in L2 learnersâ writings is crucial since it is one type of cohesiveÂ devices. This paper aims to find the cohesive devices of conjunctions used by theÂ learners. Through analyzing eight learnersâ essays, the writer found 37 forms and 12Â types of conjunctions in the learnersâ essays. The most significant form of conjunctionsÂ wasâandâ, whereas the most significant types of conjunction as âadditionâ. Moreover,Â the writer also found some inappropriate use of conjunctions, which are groupedÂ into five, namely, unclassified, wrong mechanism, L1 interference, wrong forms ofÂ conjunctions, and grammatical error.Â DOI: https://doi.org/10.24071/llt.2015.180106